Ethnic‐racial socialization in the context of the achievement gap discourse. (20th December 2021) - Kuchirko, Yana; Nayfeld, Irena
Abstract: Messages about race and ethnicity are embedded in everyday settings and interactions. Research on ethnic‐racial socialization (ERS) commonly centers on relationships between youth and their teachers, parents, and peers as contexts of socialization. We propose another context for ERS: Discourse. We suggest that messages about race and ethnicity are part of larger, uncontested and unacknowledged Discourses—with an uppercase D—which refer to semiotic processes occurring at multiple layers of cultural, ideological, and social contexts. We zero in on the achievement gap discourse (AGD), a prevailing, uncontested and unacknowledged discourse that is rooted in U.S. racial hierarchies. We suggest that messages about ethnicity and race are conveyed to students and teachers through four avenues relevant to the AGD (1) Benchmarks and standards for student learning; (2) Curriculum and pedagogy; (3) Language around educational performance, and (4) Spaces of learning. We conclude with future directions that examine the relation between the AGD and ERS.